Software architect - Bell, Michael (John Wiley & Sons, Inc., 2023)
A strategic state-of-the-art software architecture manual for all skill levels In Software Architect, veteran enterprise and solution architect Michael Bell delivers a hands-on playbook of best practices for aspiring and practicing software architects, seeking to improve their software design, integration, communication, presentation, and knowledge acquisition skills. He explores the career enablement, career planning, self-training, and self-improvement topics you'll need to increase your ability to offer powerful and effective business and technological solutions. In the book, you'll learn how to help companies promote business and technological transformation by implementing modern and first-class software design, deployment, integration, and operations. Software Architect also includes: A modern software architect's toolbox that includes best practices for multi-dimensional software design and integration in an enterprise quantum computing ecosystem A breakdown of the various types of software architects, as well as useful self-assessments for aspiring and practicing professionals Skill acquisition strategies for software architects along with strategic approaches to ace software architecture interviews An indispensable manual for aspiring to be architects, software architects-in-training, and practicing software architects. Software Architect is an essential read for anyone hoping to improve their ability to deliver robust business and technical solutions to enterprises everywhere.